The "Metropolitan Thesis" and the Writing of Canadian Urban History - Davis, Donald (Urban History Review / Revue d'histoire urbaine, 1985)
This article deals with the concept of metropolitanism as found in the writings of Canadian historians and geographers. It argues that, contrary to common belief, there is no single metropolitan ''thesis." Rather there are different approaches to the metropolis-hinterland relationship, five of which are discussed in the article. These vary, it is shown, in their assumptions about individual autonomy, the power of the metropolis, the mutability of the metropolis-hinterland relationship, and the universality of the metropolitan phenomenon. The failure to recognize the variety of approaches to metropolitanism has, it is argued, retarded the development of urban studies in Canada. While admitting the possibility of progress once historians have clarified their differences concerning metropolitanism, the article suggests, nonetheless, that urban historians might do better by abandoning the metropolitan approach altogether, given its indeterminancy, its avoidance of fundamental class relationships, as well as its inherent manicheanism and spatial bias.